Legal Systems and Earnings Quality: The Role of Auditor Industry Specialization - LIM, Chee Yeow (Institutional Knowledge at Singapore Management University, 2007)
This paper extends prior studies in auditor industry specialization to an international setting and examines if the impact of industry specialist auditors on earnings quality is dependent on the legal environments. Using data for 28 countries over 20 industries from 1993 to 2003, we find that clients of industry specialist auditors have lower discretionary current accruals and higher earnings response coefficients than clients of nonspecialist auditors. In addition, we find that the impact of auditor industry specialization on earnings quality increases as the legal environment weakens. Collectively, the results suggest that the benefits from engaging the services of industry specialist auditors increase as a country's legal environment shifts from a strong to a weak environment. Our results are robust to the inclusion of additional control variables.